A STUDY ON APPLICATIONS AND CONCEPTS OF SENTIMENT ANALYSIS - Uma, P; Aloysius, A (International Journal of Computer Sciences and Engineering, 2025)
At present, the stage of Internet has changed the way that the people express their views and opinions in Social Media. Millions of people are using social network sites like Facebook, Twitter, Google Plus, etc. to express their emotions, opinion and share views about their daily lives. Through the online communities, sellers get an interactive media where consumers inform and influence others by online forums. Social media is generating a large volume of sentiment rich data especially in the form of tweets, status updates, blog posts, comments, reviews, etc. Sentiment analysis has become a very popular field of research and lot of researchers have explored this field but still, there are many issues as sentiment analysis processes text-based unstructured data. The dictionary-based approach takes less processing time than supervised learning approach but accuracy is not up to the mark. Supervised learning approach provides better accuracy and it is found that sentiment classifiers are severely dependent on domains or topics. In this research paper, applications of sentiment analysis, types of approaches present, and evaluation metrics’ involved in sentiment analysis are discussed briefly.